2022
DOI: 10.1111/os.13535
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perpendicular to the Coronal Plane versus Medial Inclination for C2 Pedicle Screw Insertion Assisted by 3D Printed Navigation Template

Abstract: Objective C2 pedicle screw insertion is very important in posterior upper cervical surgery. The traditional screw placement technique requires us to consider both medial inclination and cephalad angle, it is difficult to operate intraoperatively. This paper is to explore a novel method of C2 pedicle screw placement compared with traditional C2 pedicle screw. Methods A total of 44 patients diagnosed with atlantoaxial fracture or instability from May 2018 to November 2020 were involved in this retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The greatest advantage of 3D-printed navigation templates in orthopedic surgery is the improved accuracy of internal fixation placement. Wu et al [ 14 ] found that navigation templates assisted the C2 pedicle screw insertion resulting in a more accurate and safe procedure than traditional techniques. Similar results regarding the improvement of surgical accuracy by navigation templates have been reported in other studies [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The greatest advantage of 3D-printed navigation templates in orthopedic surgery is the improved accuracy of internal fixation placement. Wu et al [ 14 ] found that navigation templates assisted the C2 pedicle screw insertion resulting in a more accurate and safe procedure than traditional techniques. Similar results regarding the improvement of surgical accuracy by navigation templates have been reported in other studies [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%